Nanoparticles and Gut Microbiota in Colorectal Cancer - Perumal, Komathi; Ahmad, Suhana; Mohd-Zahid, Manali Haniti; Wan Hanaffi, Wan Nurhidayah; Z.A., Iskander; Six, Jean-Luc; Ferji, Khalid; Jaafar, Juhana; Boer, Jennifer C.; Plebanski, Magdalena; Uskoković, Vuk; Mohamud, Rohimah (Frontiers in Nanotechnology, 2021)
Recent years have witnessed an unprecedented growth in the research area of nanomedicine. There is an increasing optimism that nanotechnology applied to medicine will bring significant advances in the diagnosis and treatment of various diseases, including colorectal cancer (CRC), a type of neoplasm affecting cells in the colon or the rectum. Recent findings suggest that the role of microbiota is crucial in the development of CRC and its progression. Dysbiosis is a condition that disturbs the normal microbial environment in the gut and is often observed in CRC patients. In order to detect and treat precancerous lesions, new tools such as nanotechnology-based theranostics, provide a promising option for targeted marker detection or therapy for CRC. Presence of gut microbiota influences the route of biomarker detection and the route of the interaction of nanoparticle/drug complexes with target cells, the development of nanoparticles with appropriate sizes, morphologies, chemical compositions and concentrations might overcome this fundamental barrier. Metallic particles are good candidates for nanoparticle-induced intestinal dysbiosis, but this aspect has been poorly explored to date. Herein, we focus on reviewing and discussing nanotechnologies with potential applications in CRC through the involvement of gut microbiota and highlight the clinical areas that would benefit from these new medical technologies.